2006
DOI: 10.1177/0093650205283101
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Evaluations of Emotional Support Skills, Goals, and Behaviors

Abstract: The present study assessed how people residing in China evaluate the emotional support they receive and provide, as well as whether gender-related influences on emotional support exhibited in American samples are also present among Chinese. Participants (253 native Chinese) responded to a questionnaire that assessed the value placed on emotional support skills, the importance of goals typically pursued in emotional support situations, the appropriateness of distinct coping strategies for providing emotional su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“… 3. Messages were similar to those used in multiple comforting studies (Burleson, Holmstrom, & Gilstrap, 2005; Burleson, Liu, Liu, & Mortenson, 2006). They were rated appropriately as low person-centered (LPC), moderate person-centered (MPC), or high person-centered (HPC) messages by two expert judges.…”
mentioning
confidence: 99%
“… 3. Messages were similar to those used in multiple comforting studies (Burleson, Holmstrom, & Gilstrap, 2005; Burleson, Liu, Liu, & Mortenson, 2006). They were rated appropriately as low person-centered (LPC), moderate person-centered (MPC), or high person-centered (HPC) messages by two expert judges.…”
mentioning
confidence: 99%
“…Salient scholarship has explored the effects of sex, culture, and ethnicity in relation to emotional support skills, messages, goals, behaviors, and values during relationship development (e.g., Burleson, 2003;Burleson, Liu, Liu, & Mortenson, 2006;Xu & Burleson, 2001). Although relatively sparse, comforting communication has also been studied within organizational and team contexts (e.g., Ray, 1991Ray, , 1993Sass & Mattson, 1999;Zimmerman & Applegate, 1992).…”
Section: Social Supportmentioning
confidence: 99%
“…31 It has also been found that Chinese women value emotional support skills more than Chinese men. 32 However, sex differences in the relationship between emotional support and self-rated health of the elderly has not been fully investigated, especially in China.…”
Section: Introductionmentioning
confidence: 99%